Frequency of Abnormal Fecal Biomarkers in Irritable Bowel Syndrome. Issue 3 (May 2014) - Goepp, Julius; Fowler, Elizabeth; Mcbride, Teresa; Landis, Darryl
Primary Study Objective: Determine the frequency of abnormal fecal biomarker test results in patients with 13 irritable bowel syndrome (IBS)—related ICD-9 (International Statistical Classification of Diseases and Related Health Problems) codes. Study Design: Quantitative review of de-identified records from patients in whom IBS was a possible diagnosis. Methods: Records were selected for analysis if they included any of 13 IBS-related diagnostic codes and laboratory test results of fecal testing for all biomarkers of interest. Data collection was restricted to one 12-month period. Frequency distributions were calculated to identify rates of abnormal results for each biomarker within the total number of tests conducted in the eligible population. Results: Two thousand, two hundred fifty-six records were included in the study, of which 1867 (82.8%) included at least one abnormal value. Quantitative stool culture for beneficial bacteria (Lactobacillus and Bifidobacterium) indicated low growth suggestive of intestinal dysbiosis in 73.1% of records, followed by abnormally elevated eosinophil protein X (suggestive of food allergy) in 14.3%, elevated calprotectin (suggestive of inflammation) in 12.1%, detection of parasites in 7.5%, and low pancreatic elastase (suggestive of exocrine pancreatic insufficiency) in 7.1%. Conclusions: Abnormal fecal biomarkers are prevalent in patients with diagnoses suggestive of IBS. Abnormal fecal biomarker testing, if confirmed in additional independent clinical trials, could substantially reduce the economic costs associated with diagnosis and management of IBS.